mtDNA G10398A variation provides risk to type 2 diabetes in population group from the Jammu region of India - Sharma, Varun (Meta Gene, 2014)
Mitochondrion plays an integral role in glucose metabolism and insulin secretion. Mitochondrial electron-transport chain (ETC) is involved in adenosine triphosphate (ATP) generation and ATP mediated insulin secretion in pancreatic β-cells. β-cell dysfunction is a critical component in the pathogenesis of type 2 diabetes (T2D). The mtDNA G10398A variation (amino acid change: Alanine → Threonine) within the NADH dehydrogenase (ND3) subunit of complex I of mtDNA ETC, has emerged as a variation of clinical significance in various disorders including T2D. This variation is supposed to result in altered complex I function, leading to an increased rate of electron leakage and reactive oxygen species (ROS) production, which might cause β-cell damage and impaired insulin secretion. The aim of the study was to explore the association of mtDNA G10398A variation with T2D in a total of 439 samples (196 T2D cases and 243 healthy controls) belonging to the Jammu region of Jammu and Kashmir (J&K). The candidate gene association analyses showed significant association of mtDNA G10398A variant with T2D and the estimated odds ratio (OR) was 2.83 (1.64–4.90 at 95% CI) in the studied population group. The extent of genetic heterogeneity in T2D and diversity of the Indian population groups, make such replication studies pertinent to understand the etiology of T2D in these population groups.